Analysis of technical vocabulary size among engineering undergraduates based on year of study and English proficiency level at Universiti Malaysia Pahang - Amri Muaz, Azmimurad; Najah, Osman (Universiti Malaysia Pahang, 2018)
English for Specific Purposes (ESP) was designed to fulfil the needs of learners learning languages in specific disciplines. ESP concerns on words or terms that are created specifically or have their own definition in specific fields. As engineering students read abundance of technical texts such as manuals and reports that contain numerous technical terms that have specific meaning in the engineering field, the vocabulary knowledge of technical terms is essential for them in order to understand and comprehend the texts. However, engineering students were found to have difficulties whenever they encountered texts filled with abundance of technical terms. Hence, this study aims to investigate the vocabulary size of technical,vocabulary among engineering students at Universiti Malaysia Pahang. This research employs two instruments which are technical vocabulary test and semi-structured interview. The test was used in collecting quantitative data while the semistructured interview was used in collecting qualitative data. The test was administered to 150 students majoring in five different engineering courses who were currently on their third and fourth year of study whereas the interview involved 12 students from five respective engineering courses. The findings show that engineering undergraduates did not have adequate knowledge of technical terms and there was a significant difference in technical vocabulary size among engineering undergraduates based on English language proficiency level. However, there was no significant difference found in technical vocabulary size among engineering undergraduates when they are compared based on their year of study.